Literature Review: Implementation of Digital Comics-Assisted Peace Guidance to Prevent Bullying in High School Students - Maulana Ichsan Kurniawan; Wahyu Nanda Eka Saputra; Irvan Budhi Handaka; Muya Barida; Alif Muarifah (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2025)
This study aims to examine the implementation of digital comic-assisted peace guidance in preventing bullying among high school students. The method used is a literature study with a qualitative approach. Data was collected through a review of scientific articles and books from 2014 to 2025 relevant to the keywords peace, comics, violence, and bullying. The results of the study show that peace guidance with a group guidance model using discussion strategies, role play, and visual media such as film and photography are effective in shaping students' peaceful mindset. Digital comics that contain peace values based on local culture, religion, and inspirational figures, both fiction and non-fiction, have proven to be able to be an educational medium that strengthens students' understanding of the importance of peace and reduces the tendency to violent behavior. This study recommends the use of digital comics as an innovative medium in guidance and counseling services in schools to create a safe and bullying-free learning environment.